DEVELOPMENT OF ETHNO-STEM BASED MODULES INTEGRATED WITH CREATIVE THINKING ON ELEMENTS, COMPOUNDS AND MIXTURES MATERIAL - Lubis, Erina Debora Mastauli; Djulia, Ely; Samdinal, Samdinal (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The limited relevance of science learning and the dominance of conventional teaching methods have led to low creative thinking skills among students. This study aims to develop an Ethno-STEM-based module integrated with creative thinking skills on the topic of elements, compounds, and mixtures. The development model used is the 4D model (Define, Design, Develop, and Disseminate), limited to expert validation, teacher and student responses. The module integrates local wisdom and cultural contexts with STEM learning stages, fostering fluency, flexibility, originality, and elaboration. The validation results show that the module meets the